2021
DOI: 10.1177/2399808321991536
|View full text |Cite
|
Sign up to set email alerts
|

Public transport availability inequalities and transport poverty risk across England

Abstract: The general transit feed specification is becoming a popular data format for the publication of public transport schedules, making possible the collection of a nation-wide public transport schedule dataset, which enables monitoring of transit supply at an up-to-date and more precise level across a country than previously possible. In this paper, we use general transit feed specification data to measure local-scale public transport availability across England based on service frequency and spatial proximity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The lowest level of satisfaction was revealed regarding affordability. This corresponds with earlier research where the cost of a ticket for travel affects the risk of "transport poverty" [22][23][24][25] and must be under hard control. The ability to get the service itself (Availability) and its attributes: bus waiting time, bus punctuality, bus frequency, and bus schedule, also affect passenger dissatisfaction.…”
Section: -Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The lowest level of satisfaction was revealed regarding affordability. This corresponds with earlier research where the cost of a ticket for travel affects the risk of "transport poverty" [22][23][24][25] and must be under hard control. The ability to get the service itself (Availability) and its attributes: bus waiting time, bus punctuality, bus frequency, and bus schedule, also affect passenger dissatisfaction.…”
Section: -Discussionsupporting
confidence: 82%
“…For example, in a series of transport studies in the Bogotá Region (Colombia), an analysis of the impact of poverty on transport accessibility showed that the higher the household income, the better the transport accessibility [19][20][21]. As some researchers have demonstrated in their studies, even in prosperous countries there is a problem of economic inequality in the provision of public transport and the risk of "transport poverty" [22][23][24][25].…”
Section: Affordabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The service area is created from a road-network buffer, rather than a circular buffer which is used in most existing studies (Figure A3). The road-network buffer more accurately captures each stations' service area [41] and is defined as 800 m, as it is typically used as the upper limit of where most users will travel to access rail stations by foot [42]. Due to the simplicity of buffers, they do induce bias where the influence of neighbourhoods beyond the 800 m buffer is not considered [41].…”
Section: Supplementary Data and Station Service Areasmentioning
confidence: 99%
“…The road-network buffer more accurately captures each stations' service area [41] and is defined as 800 m, as it is typically used as the upper limit of where most users will travel to access rail stations by foot [42]. Due to the simplicity of buffers, they do induce bias where the influence of neighbourhoods beyond the 800 m buffer is not considered [41]. This could influence the interpretation of the results, particularly with the segregated nature of Chicago's neighbourhoods, as mainly African American neighbourhoods live near rail stations [10].…”
Section: Supplementary Data and Station Service Areasmentioning
confidence: 99%